1993
DOI: 10.1113/jphysiol.1993.sp019501
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the calcium pump by high cytosolic Ca2+ in intact human red blood cells.

Abstract: Ancillary new findings demonstrated that, unlike the situation with a-buffers, Co2+ displaced Ca2+ from the cell-incorporated calcium chelator benz-2, and that benz-2 incorporation had no effect on Co2+-exposed Ca2+ pump desaturation. This validates the use of benz-2 to study Ca2+ pump kinetics in intact cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The washed, ionophore-free packed RBCs (about 75% Hct) were resuspended (final Hct, about 14%) in 90K medium supplemented with inosine in a magnetically stirred glass vial in a water bath at 37°C; this immediately reactivated Ca 2+ extrusion 27 (t = 0) at the pump V max rate of each RBC. At 15- to 30-second intervals, 0.5 mL samples of this suspension were delivered into tubes containing 12 mL of 0K medium at 0°C to 4°C to instantly block further RBC Ca 2+ extrusion and trap their residual Ca 2+ content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The washed, ionophore-free packed RBCs (about 75% Hct) were resuspended (final Hct, about 14%) in 90K medium supplemented with inosine in a magnetically stirred glass vial in a water bath at 37°C; this immediately reactivated Ca 2+ extrusion 27 (t = 0) at the pump V max rate of each RBC. At 15- to 30-second intervals, 0.5 mL samples of this suspension were delivered into tubes containing 12 mL of 0K medium at 0°C to 4°C to instantly block further RBC Ca 2+ extrusion and trap their residual Ca 2+ content.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the intrinsic measurement error of the reported Hb A1c values is within the size of the points in the figures below. Preliminary experiments (not shown) using Co 2+ instead of albumin washes 27 to terminate ionophore-mediated Ca 2+ fluxes 30 showed that Co 2+ alters the size and shape of the Hb A1c peaks, suggesting that Co 2+ might crosslink Hb with some other cell or lysate component that coeluted with genuine glycosylated Hb A1c. This precluded Co 2+ use when measuring Hb A1c.…”
Section: Methodsmentioning
confidence: 99%
“…Four millilitres of this suspension were equilibrated in a tonometer at 37 0C for 10 min with either 02 or N2. Ionophore A23187 was added during this period to give a concentration of -100 ,umol (1 cells)-', which generates Ca2+ fluxes far above those of saturated Ca2`pumps and ensures a rapid and nearly total Ca2+ equilibration even in substrate-fed cells (Simonsen & Lew, 1980 (Pereira, Samellas, Tiffert & Lew, 1993). Another limitation is that medium and cell pH vary in parallel, preventing distinction of intra-and extracellular effects.…”
Section: Methodsmentioning
confidence: 99%
“…6 Ca2+ permeability of the membrane was about 10-4 cm S-1 [CaT]h load of 28 umol (340 g Hb)-'. Higher loads were avoided to prevent the inhibitory effects of high [CaT]i on the Ca2P pump Vmax (Pereira, Samellas, Tiffert & Lew, 1993). At t = 2 min, CoC12 in water was added from a 10 mm stock solution to give a final concentration of -40 uM in the suspension.…”
Section: Experimental Designmentioning
confidence: 99%